2012
DOI: 10.1136/jramc-158-04-07
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Accidents In Greek Armed Forces In Evros County

Abstract: This study highlights the increased likelihood of occupational accidents among military personnel with lower rank and lower level of education, less working experience (fewer years of service) and less military training (conscripted and professional soldiers). The existence of occupational accidents in the workplace, civilian or military, creates the need for the adoption of policies for the protection of workers and the organization of occupational preventive services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…41 This finding is consistent with Bena et al, who found that injury rates decrease with increased time spent in the current job and those of Malliarou, which found that less working experience increased the probability of occupational injuries among military personnel. 16,42 Other risk factors associated with injuries in this study were educational level and job exposure. In agreement with prior studies, higher educated workers reported the lowest accident rate and were the most compliant with the safety process.…”
Section: Acknowledgmentsmentioning
confidence: 74%
“…41 This finding is consistent with Bena et al, who found that injury rates decrease with increased time spent in the current job and those of Malliarou, which found that less working experience increased the probability of occupational injuries among military personnel. 16,42 Other risk factors associated with injuries in this study were educational level and job exposure. In agreement with prior studies, higher educated workers reported the lowest accident rate and were the most compliant with the safety process.…”
Section: Acknowledgmentsmentioning
confidence: 74%
“…Military personnel can face serious injuries and even fatal injuries,1–3 and such accidents, which cause non-combat losses, are factors causing difficulties in maintaining military combat power 4–6. Furthermore, in the event of an accidental death, the incident itself may affect the morale of the armed forces or may result in the nation losing confidence in or withdrawing support from the military 7…”
Section: Introductionmentioning
confidence: 99%